Kinetic-Catalytic Spectrophotometric Determination of Vanadium(V) Using the Oxidation of Pyronin G by Bromate - Keyvanfard, Mohsen (Asian Journal of Chemistry, 2010)
A new, simple, sensitive and selective catalytic spectrophotometric method was developed for the determination of ultra trace amounts of vanadium(V). The method is based on the catalytic effect of vanadium(V) on the oxidation of pyronin G by bromate in acidic medium. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of pyronin G at 545 nm with a fixed-time method. The decrease in the absorbance of pyronin G is proportional to the concentration of vanadium(V) in concentration range 0.06-10 ng/mL, with a fixed time of 0.5-5.5 min from initiation of the reaction.The limit of detection is 0.034 ng/mL vanadium(V). The relative standard deviation of 5.0 and 10.0 ng/mL vanadium(V) was 2.1 and 2.7 %, respectively. The method was applied to the determination of vanadium(V) in natural water.